Produção, caracterização funcional e imunogênica de uma proteína dermonecrótica recombinante 9recLiD1) da aranha Loxosceles intermédia - Liza Figueiredo Felicori Vilela (2008)
In the present study the recombinant form (rLiD1) of a dermonecrotic protein from the Brazilian Loxosceles intermedia spider venom was expressed in Escherichia coli and purified by reversed-phase HPLC. Twenty five mg of rLiD1 was produced from liter of bacterial culture. The molecular weight of rLiD1 was verified by mass spectrometry (32,758 Da). rLiD1 displayed dermonecrotic and platelet aggregation activities. However, very low sphingomyelinase D and complement-dependent haemolytic activities were observed. Immunized BALB/c mice with rLiD1 developed an antibody response that reactead by ELISA with L. intermedia crude venom and cross-reacted with L. gaucho and L. laeta whole venoms. In vivo protection assay showed that 75% of the immunized mice resist to the challenge by 2.5 LD50 of L. intermedia venom (25 ìg). To characterize epitopes associated with protective antibodies, we prepare synthetic 15 mer overlapping peptides covering the complete amino acid sequences of the LiD1. Immunoassays revealed one antigenic region in the N-terminal of the molecule. The amino acid sequence of this epitope was found in other dermonecrotic proteins and some of its residues have been implicated with the active site of the toxin. This epitope was synthesized and used to raise antibodies in rabbits. Anti-peptide antibodies showed reactivity with rLiD1 and with L. intermedia whole venom and induced protections against dermonecrotic activity. Analysis with anti-Loxosceles serum (CPPI) revealed six different epitope regions. One epitope representative of each region was synthesized and utilized as antigenic mixture to immunize rabbits. Anti-peptides antibodies protect in vitro and in vivo dermonecrotic activity of rLiD1 at order of 80% and 60%, respectively. Therefore, antibodies against rLiD1 neutralized 100% of this activity. To evaluate the cross reactivity of anti-rLiD1 rabbit antibodies against others L. intermedia proteins, overlapping peptides of five proteins from dermonecrotic family (LiRecDT2, LiRecDT4, LiRecDT5, Loxtox i5, Loxtox i7) were synthesized. Anti-rLiD1 antibodies cross-react with all of them, showing two conserved regions. One of these regions was also found in SmaseI of L. laeta venom. Thirty-five continuous peptides mimicking discontinuous regions of rLiD1 were designed by using the bioinformatic tool PEPOP and prepared by Spot synthesis. Antibodies anti-rLiD1 recognized one discontinuous-continuous region. As conclusion, we can suggest that the use of synthetic peptides can be a good approach for anti-venom development.